A New Keynesian model with unemployment: The effect of on-the-job search - Zeynep Kantur; Kerim Keskin (Kiel Institute for the World Economy (IfW), 2017)
Although New Keynesian models with labor market frictions found an increase in unemployment and a decrease in labor market tightness in response to a positive technology shock (which appears to be in line with recent empirical findings), the volatilities of unemployment and labor market tightness are not as high as their empirical counterparts. This calls for the introduction of new tools that will amplify the volatilities of these variables. This paper contributes to the theoretical literature by studying the effect of employment-to-employment flows in a New Keynesian model with labor market frictions. In that regard, the authors assume two types of firms which offer different wage levels, thereby incentivizing low-paid agents to search on-the-job. Differently from the literature, the main source of wage dispersion is the assumption of different bargaining powers of firms motivated by the strength of labor unions. The authors show that the proposed model generates a higher volatility of unemployment and labor market tightness in response to a positive technology shock compared to the model without on-the-job search without causing a change in the responses of the other variables.
Keywords: E12; E24; E32; J63; J65; 330; New Keynesian model; employment-to-employment flow; unemployment fluctuations; the Shimer puzzle; search and matching